ISLAM DAN HAK ASASI MANUSIA (TAFSIR MAUDHU`I) - Naufal Adlinsyah; Nisa Fadhilah Salma; Reza Fitriansyah Putra (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2023)
The paper "Islam and Human Rights" discusses the relationship between human rights and Islamic teachings, as well as the dynamics of the debate on harmonization between Islamic practice and human rights. The paper is generated through a literature review and case studies that attempt to provide diverse views on whether the concept of human rights can be reconciled with Islamic principles. The paper explains that in Islamic teachings, the principles of human rights are explicitly recognized, such as the principles of equality and justice for all human beings. However, there is often a view that Islamic teachings can be a threat to human rights due to contradictions in certain issues such as the death penalty, gender discrimination, and others. This paper seeks to provide a better explanation and understanding between Islam and human rights in order to create a harmonious dialogue and minimize polarization of views. Therefore, this paper can be a basis for readers to gain a more complete view of the harmonization efforts between Islam and human rights.